Pengaruh Model Flipped Learning Versus Model Direct Learning dan Motivasi Belajar terhadap Hasil Belajar Mata Pelajaran Bahasa Inggris Siswa Kelas X SMK Negeri 1 Driyorejo Gresik - Lia Rizqi; Ibut Priono Leksono; Ujang Rohman (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
Differences in student learning outcomes become a reference in drawing research conclusions. The learning outcomes are grouped based on two variables. Learning outcomes based on the application of learning models and learning outcomes based on the level of learning motivation possessed by students. The type of research used is experimental research. Data collection using written tests and questionnaires. Written test instruments are used to collect data in the form of student learning outcomes. This test is given before learning activities begin and at the end of learning. The questionnaire instrument was used to collect data in the form of students' motivational values and was given before the learning activities began. Furthermore, the research data were analyzed using Two-way Anava. This study has three hypotheses. Based on the results of data processing, it was found that the first hypothesis was accepted, namely that there were differences in the effect of the learning model on student learning outcomes; the second hypothesis is accepted, namely that there is an influence of learning motivation on student learning outcomes; and the third hypothesis is rejected, which means there is no interaction with the Flipped Learning and Direct Learning models and learning motivation on student learning outcomes in English subjects. Suggestions that can be conveyed through this research are that this kind of research should be carried out with a longer research period, using different materials and at different levels. It is possible to obtain generalization of research results. The use of more interesting learning media and effective learning plans will greatly assist in the learning process.